1,2-Dihydroxy-9H-Xanthen-9-One, a Multifunctional Nature-Inspired Active Ingredient - Ana Jesus; Sara F. Vieira; Gonçalo Brites; Mylène Carrascal; Helena Ferreira; Nuno M. Neves; Honorina Cidade; Madalena Pinto; Emília Sousa; Isabel F. Almeida; Maria T. Cruz (Cosmetics)
Incorporating antioxidants into cosmetics is the mainstay for developing new products to mitigate skin aging. However, identifying novel multifunctional antioxidant ingredients with additional relevant properties that block the skin hallmarks of aging is a very striking strategy. Many natural compounds, including xanthones, have demonstrated biologically notable properties. In particular, 1,2-dihydroxy-9H-xanthen-9-one (1,2-DHX) has inhibitory activity against skin enzymes, and metal-chelating and radical-scavenging activities. Therefore, 1,2-DHX is an attractive molecule for cosmetic purposes. With this goal in mind, the anti-inflammatory, antioxidant, and anti-allergic potentials of 1,2-DHX were investigated. 1,2-DHX demonstrated anti-inflammatory properties by inhibiting the synthesis of specific pro-inflammatory mediators, including interleukin-6 (IL-6) and prostaglandin E2 (PGE2), in human macrophages. This xanthone did not elicit sensitization reactions and did inhibit allergic reactions triggered by a strong skin allergen, suggesting its potential as an anti-allergic compound. 1,2-DHX also revealed mitochondrial antioxidant activity by mitigating rotenone-induced oxidative stress in macrophages by up to 40%. Overall, 1,2-DHX displayed a safety profile and noteworthy biological activities, highlighting its multifunctional profile as an active cosmetic ingredient with anti-inflammatory, antioxidant, and anti-allergic properties.